PENGARUH LINGKUNGAN USAHA DAN KEBIJAKAN PEMERINTAH TERHADAP KINERJA DAN TUJUAN PEMBANGUNAN PERIKANAN JAWA TENGAH - Abdul Kohar Mudzakir; Mulyono S. Baskoro; Bunasor Sanim; Soepanto Soemokaryo; Sugeng H. Wisudo (Buletin PSP, 2008)
Need to be improved the existence of change for direction and development target in national, regional and international level, claim sensitivity of fishery sector to anticipate the condition. The objectives of the research are analyze fishery effort by taken into considerations: environmental influence, central government policy, local government policy to fishery sector performance and development target of Central Java fishery, and dominant factor which influence. To analyze complicated relation of each variable of fishery effort environment, central government policy, local government policy, capture fishery effort performance, processing industry performance, and development target of central Java fishery are used structural equation model (SEM) analysis with AMOS version 6 software. Collecting data conducted to 228 responder by using closed questionnaire which designed so responder gave opinion by choosing scale number which had scale 1-5 liker scale. The result show chi-square value (1128,994), probability (0,000), CMIN/ DF (1,634), GFI (0,805), AGFI (0,769), TLI (0,912) and RMSEA (0,053), at recommended value gyration, so the model have fit. From 15 examined hypothesis, there are 6 significant hypothesis that are hypothesis 6, hypothesis 7, hypothesis 8, hypothesis 11, hypothesis 12 and hypothesis 15, while hypothesis 1, hypothesis 2, hypothesis 3, hypothesis 4, hypothesis 5, hypothesis 9, hypothesis 10, hypothesis13, and hypothesis 14, proven not significant. Dominant factor in efficacy to development target of Central Java fishery is central government policy, with the component are training policy and accessed tuition.